Sosialisasi Media Pembelajaran Matematika Berbasis Interaktif Pokok Pembahasan Bangun Ruang Kelas V SD Negeri 02 Indarung - Lili Rismaini; Mishbah Ulhusna; Syelfia Dewimarni (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
This Community Service (PKM) is one of theTridharma of Higher Education. This PKM is proposed to carry out activities that are socializing interactive-based mathematics learning media. This activity is proposed with the consideration that students still lack knowledge about interactive-based learning media methods in mathematics lessons. Therefore, with this PKM activity, it can make it easier for students to face mathematics learning. The coaching, socialization and education activities that have been carried out at SD Negeri 02 Indarung have run smoothly in accordance with the desired targets and outcomes. Based on the results of the socialization of mathematics learning through interactive-based learning media in the Mathematics Subject of Grade V Students of SD Negeri 02 Indarung Padang, it provides benefits, namely it can eliminate student boredom in learning mathematics, providing variety at SD Negeri 02 Indarung Padang. This means that there is a significant influence on the socialization of mathematics learning through the Socialization of Interactive-Based Mathematics Learning Media Topic of Class V SD Negeri 02 Indarung